Oscillations and coherent radiation of harmonics in radiation spectrum of system of electrons moving in spiral in medium - Konstantinovich, A.V.; Konstantinovich, I.A. (Вопросы атомной науки и техники, 2011)
Using the Lorentz self-interaction method completing by Dirac hypothesis it is investigated the spectral distribution of the radiation power for the system of electrons moving along a spiral in transparent isotropic medium. The overlapping between neighbour harmonics as well as oscillations in the spectral distribution of one, two, three, and four electrons radiation power are studied for the case when the transversal component of electron velocity is bigger than the light phase velocity in medium but still less than the light velocity in vacuum. The effect of coherence in the spectrum of synchrotron-Cherenkov radiation for the system of two, three and four electrons is analyzed.